(untitled) (Ibrahim Cardiac Medical Journal, 2011)
A one year and three months male child having Total Anomalous Pulmonary Venous Connection (TAPVC) presented at Ibrahim Cardiac Hospital and Research Institute with repeated cough, tachypnoea, fever, failure to thrive & diaphoresis particularly during feeding with a mild degree of cyanosis without any evidence of heart failure. He underwent successful rerouting of pulmonary veins to left atrium (LA). The procedure consisted of side to side wide anastomosis between confluence of pulmonary veins (CPV) and left atrium with the division and ligation of vertical vein at its opening to left innominate vein and closure of atrial septal defect (ASD). The patient is doing well without any symptoms at followup. Key words: TAPVC; CPV; Vertical vein Ibrahim Card Med J 2011; 1(1):56-58